Is Reinke's Edema a Precancerous Lesion? Histological and Electron Microscopic Aspects - Garcia Martins, Regina Helena [UNESP]; Fabro, Talexandre Todorovic [UNESP]; Domingues, Maria Aparecida Custódio [UNESP]; Chi, Andrea Peiyun [UNESP]; Gregorio, Elisa Aparecida [UNESP] (Mosby-elsevier, 2009)
The objectives of this study were to evaluate morphologic alterations and precancerous lesions in Reinke's edema. Patients included were 54 smokers with bilateral Reinke's edema submitted to surgery in the Otolaryngology Department, Botucatu Medical School, São Paulo State University, Brazil, between 2002 and 2006. All specimens were evaluated by light microscopy and five contralateral lesions were also evaluated by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The main histological alterations were edema (100%), inflammation (81.48%), basal membrane (bm) thickening (77.77%), and vessel proliferation (75.92%). Epithelium alterations were classified as grade 0 (11.11%), grade 1 (70.37%), grade 2 (14.81%), and grade 3 (3.70%). In the case included in grade 3 classification, microinvasive carcinoma was detected. SEM showed epithelial surface with some cellular desquamation, few microridges, and a polished and impermeable surface aspect. TEM showed epithelial hyperplasia, basal cells with different sizes, widening of the intercellular spaces, abnormal desmosome architecture, thickening of the bm, some electron-dense vesicles, and points of interruption. The morphological alterations presented in this study are not specific to Reinke's edema but this lesion can be the site of different grades of dysplasia and carcinoma, justifying the importance of periodic laryngeal endoscopic exams and meticulous histological analysis.
Keywords: Carcinoma; Dysplasia; Histology; Reinke's edema; Morphology